Protein restriction during lactation causes transgenerational metabolic dysfunction in adult rat offspring - Vargas, Rodrigo; Martins, Isabela Peixoto; Matiusso, Camila Cristina Ianoni; Casagrande, Raiana Aparecida; Zara, Camila Benan; Huppes de Souza, Anna Carolina; Horst, William Pereira; Sieklicki, Taina Cristine; Becker, Tania Cristina Alexandrino; Lucredi, Naiara Cristina; Comar, Jurandir Fernando; Malta, Ananda; et al. (Frontiers in Nutrition, 2023)
Introduction Protein restriction during lactation can induce metabolic dysfunctions and has a huge impact on the offspring’s phenotype later in its life. We tested whether the effects of a maternal low-protein diet (LP) in rats can be transmitted to the F2 generation and increase their vulnerability to dietary insults in adulthood. Methods Female Wistar rats (F0) were fed either a low-protein diet (LP; 4% protein) during the first 2 weeks of lactation or a normal-protein diet (NP; 23% protein). The female offspring (F1 generation) were maintained on a standard diet throughout the experiment. Once adulthood was reached, female F1 offspring from both groups (i.e., NP-F1 and LP-F1) were bred to proven males, outside the experiment, to produce the F2 generation. Male F2 offspring from both groups (NP-F2 and LP-F2 groups) received a standard diet until 60 days old, at which point they received either a normal fat (NF; 4.5% fat) or a high fat diet (HF; 35% fat) for 30 days. Results At 90 days old, LPNF-F2 offspring had increased lipogenesis and fasting insulinemia compared to NPNF-F2, without alteration in insulin sensitivity. HF diet caused increased gluconeogenesis and displayed glucose intolerance in LPHF-F2 offspring compared to LPNF-F2 offspring. Additionally, the HF diet led to damage to lipid metabolism (such as steatosis grade 3), higher body weight, fat pad stores, and hepatic lipid content. Discussion We concluded that an F0 maternal protein restricted diet during lactation can induce a transgenerational effect on glucose and liver metabolism in the F2 generation, making the offspring’s liver more vulnerable to nutritional injury later in life.